Ethnicity and Power in the Soviet Union - Andrzej Wierzbicki (Проблемы постсоветского пространства, 2017)
Twenty years have passed since the dissolution of the Soviet Union. Up until the point of dissolution, the Soviet authorities and intellectual elite had attempted to build a community in order to unite all Soviet citizens in the spirit of socialist modernisation. Although it is difﬁcult to demonstrate that ‘a Soviet nation’ was successfully created [1], the attempt to build such a nation can serve as a case study through which to examine nation-building processes for constructivists as well as modernists . In addition to socialist modernisation, the Soviet nation aimed to be identiﬁed as a state, which would make it similar to the political nations dominant in western countries. Contrary to western tradition, however, it was not a nation state that provided full rights for all its citizens, but rather a socialist state that was ‘ruled by workers and peasantry’. Nevertheless, the authorities aimed to give the Soviet nation the characteristics of a speciﬁc nation state. “It was a nation that in historical terms strived, or more accurately part of which strived, to form or proclaim a particular state” [2]. While at the time of proclaiming the USSR there was no such thing as the Soviet nation, it can be assumed that it was intended to become a constructed titular nation. The majority of national communities, even created ones, have an ethnic core. However academics cannot agree on the kind of state the USSR was, to what extent it took into account the ethnicity of its multinational population, how much it reﬂected the values, culture, and interests of its largest population group (i.e., the Russians) or even whether it was a Russian national state despite the strong inﬂuence of Russian ideology and politics. Some Russian academics, especially those in nationalistic circles (e.g., Valerij Solovej) as well as western scholars such as Terry Martin and Geoffrey Hosking stressed that Russians dominated demographically and politically. However, the USSR did not aim to nurture traditional Russian values. It rather fostered the deethnicisation of Russians and the ethnicisation of non-Russian. Another group of scientists, including those from post-Soviet states (e.g., Žambyl Artykbaev, Otar Džanelidze, and Georgij Siamašvili) as well as western scholars (e.g., Rogers Brubaker) concede that positive processes such as the allotment of territory to republics and other territorial units, the constitution of authority and administrative apparatus, and the formation of the elites once characterised the ethnic history of the USSR. All these processes, however, were dominated by a lack of sovereignty, a loss of national identity, and damage to the living environment. Georgia rather than the USSR has always been regarded by the Georgian people as their mother country. The Soviet Union, which was considered to be a voluntary union of equal republics, was in fact an artiﬁcial creation that non-Russian nations were forced to join. The majority of Georgians did not therefore claim the USSR as their homeland: ‘The USSR was for its nations a socio-political state not a homeland’ [3]. Non-Russian citizens in the Soviet Union perceived the Russians to be a state-building ‘nation’ and the USSR a Russian state. The Soviet authorities, who predicated internationalism on the Russian language and new Russian culture, actively combated ethnic nationalism (including Russian nationalism, which was associated with chauvinism and a tsarist legacy). Although Russkost was considered to be a remnant of a disgraceful past, it was nonetheless used as a tool to sovietise society. Indeed, Russian language and culture were both conducive to the assimilation of non-Russians. ‘The Great Russian nation’ was to be ‘the ﬁrst among equals’ and thus Russia provided. Soviet state with certain features of ethnicity. However, Russian characteristics were never treated as instrumental to the USSR, because the aim was to form a new socialist, national community, that was beyond ethnicity, rather than to convert the citizens of the former USSR into Russians. Soviet ideology and science thus set the direction for nationality policy in the USSR, especially in terms of forming a Soviet nation. Based on the foregoing, the present paper identiﬁes how the ethnic character of both the Soviet nation and the state.